TRANSPARANSI PENGGUNAAN ANGGARAN PADA DINAS PERUMAHAN, KAWASAN, PERMUKIMAN, DAN PERTANAHAN (DPKPP) KOTA PAREPARE (ANALISIS AKUNTANSI SYARIAH) - Tegar Fujianto (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2024)
This study aims to examine the budgeting mechanism at the Department of Housing, Area, Settlement, and Land (DPKPP) of Parepare City, the form of transparency in budget utilization, and the application of Islamic accounting principles in budget management. A qualitative approach with a phenomenological method was used, where data were collected through observation, interviews, and documentation. The results show that DPKPP Parepare City applies a mixed budgeting method between Top-down and Bottom- Up to ensure efficiency in budget preparation. Budget transparency is reflected in the use of the Regional Government Information System (SIPD) and SINAWAITU applications, which facilitate public access to budget and employee performance information. Additionally, the principles of Islamic accounting are applied through three main principles: accountability, justice, and honesty, all of which are reflected in the budget management. However, there are challenges in public understanding of technical budget reports and limited participation in the oversight process. This study suggests enhancing the use of information technology and socialization to improve future budget transparency and accountability. Islamic accounting, budget, DPKPP Parepare City, accountability principle.